Web Based Post Flood Disaster Missing People Tracking Information System - Altrad, Abdallah Mahmoud. M. (2011)
In the case of large scale disaster, such as earthquake, volcanic explosion, sea wave and flood despite those the horrible phenomenon, website post flood disaster is required not only for governmental supporters but also residents and volunteers to communicate each other. It is possible to track and manage missing people by web based disaster management information system during the post flood disaster circumstances. Thus, this study proposed web based to show information about missing people during and post flood disaster to track and report missing people. This web based has been developed using java programming and JSP which facilitates good design and services.